2012
DOI: 10.1371/journal.pone.0047442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Litopenaeus vannamei Transcriptome Using the Next-Generation DNA Sequencing Technique

Abstract: BackgroundPacific white shrimp (Litopenaeus vannamei), the major species of farmed shrimps in the world, has been attracting extensive studies, which require more and more genome background knowledge. The now available transcriptome data of L. vannamei are insufficient for research requirements, and have not been adequately assembled and annotated.Methodology/Principal FindingsThis is the first study that used a next-generation high-throughput DNA sequencing technique, the Solexa/Illumina GA II method, to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 54 publications
7
105
2
Order By: Relevance
“…GO is an international, standardized functional gene classification system, which offers a dynamically updated controlled vocabulary and a strictly defined concept to comprehensively describe the properties of genes and their products in any organism (Ye et al, 2006;Li et al, 2012). Based on the sequence homology, 18,153 (43.58%) unigenes were assigned to three functional groups based on their GO terminology: biological processes, molecular functions, and cellular components (Figure 1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…GO is an international, standardized functional gene classification system, which offers a dynamically updated controlled vocabulary and a strictly defined concept to comprehensively describe the properties of genes and their products in any organism (Ye et al, 2006;Li et al, 2012). Based on the sequence homology, 18,153 (43.58%) unigenes were assigned to three functional groups based on their GO terminology: biological processes, molecular functions, and cellular components (Figure 1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems clear that Antennapedia is present in crustaceans, as this gene was identified in two Branchiopoda (D. Pulex and Artemia franciscana) and in the amphipod Parhyale hawaiensis. In addition, this gene is present in decapoda and was detected in L. vannamei as expressed only during the gastrula stage (215 minutes post spawning) in early embryo development (Li et al, 2012).…”
Section: Proteins In P Leniusculus Hematopoiesis -A Comparison With mentioning
confidence: 99%
“…uni-bielefeld.de/rnahybrid/submission.html) (37) based on the transcriptome of L. vannamei (38). PremiR-1959 was predicted using RNA folding Form software (http://mfold.rna.albany.edu/?q=mfold/RNA-Folding-Form).…”
Section: Bioinformatics Analysis and Statistical Analysismentioning
confidence: 99%
“…Based on the transcriptome data of L. vannamei (38), the target of miR-1959 was bioinformatically predicted by RNAhybrid software. The results showed that miR-1959 was imperfectly complementary with the 2709-2733 bp region of the mRNA of the Cactus gene, the IkB homolog in L. vannamei, just within the 39UTR (Fig.…”
Section: Target Identification Of Mir-1959mentioning
confidence: 99%